Assessment Of Fetal Maturity At Various Gestational Ages Using Modified Dubowitz Scoring System - Afreen; Lubna Ejaz; Shagufta Saeed Sial; Humera Noreen; Humaira Bilqis; Saman Akhtar (Journal of Rawalpindi Medical College)
Objective: Using a modified Dubowitz scoring system, evaluate and compare the maturity of neonates born at different gestational ages into three groups: 28+0 to 35+6 weeks, 36+0 to 36+6 weeks, and 37+0 to 37+6 weeks.